Municipal Sustainability and wind projects: a comparative analysis of municipalities with investments in wind power generation in the state of Paraíba - Barbosa, Amanda de Paula Aguiar; Cândido, Gesinaldo Ataíde Cândido Gesinaldo (Sociedade & Natureza, 2018)
One of the emerging matters in studies of sustainability has been energy, considering its importance to the relations of production and consumption, as well as the negative externalities on environmental issues. In this setting, renewables emerge as an alternative to minimize the effects of its forms generation and use. In this direction, the purpose of this article is to evaluate the sustainability of a number of municipalities that had installed wind projects and initiated by the application of an indicator system. For this, was performed a longitudinal study comparing the level of municipal sustainability before and after installation of the projects. The results indicate that there was a reduction in the level of sustainability of the group of municipalities analyzed after the installation of the enterprises, which highlights the need for redefining the forms of action of all social actors involved with investments in renewable energy.Developmen